Senam Kaki untuk Penurunan Kadar Glukosa Darah pada Pasien Diabetes Melitus (Literatur Review) (Journal of Vocational Health Science, 2024)
Background: Individuals afflicted with diabetes mellitus (DM) globally constitute 8.3% of the overall world population (IDF, 2015). Diabetes Mellitus manifests as a metabolic irregularity characterized by heightened blood sugar levels and disruptions in the metabolism of carbohydrates, fats, and proteins due to deficiencies in insulin secretion and function. Purpose: The aim of this literature review was to assess the influence of foot gymnastics exercises on individuals with diabetes mellitus. Methods: The literature exploration method involved utilizing Google Scholar (2020-2023) and employing the search terms "Foot Gymnastics" AND "Diabetes Mellitus." Five journals that adhered to the predefined inclusion criteria were identified throughout the search procedure. Literature analysis findings revealed that the majority of the located journals were published in 2022, employing case study research designs. The exclusive use of Purposive Sampling was the chosen sampling method, with an observation sheet serving as the instrument. Data analysis was executed through the Wilcoxon test. Results: The comprehensive review of all journals concluded that foot gymnastics significantly contributes to lowering blood sugar levels in individuals with diabetes mellitus. This outcome aligns with Smeltzer & Bare's (2002) theory, asserting that foot exercises can effectively decrease blood sugar levels. The average reduction in blood sugar levels following foot gymnastics ranged from 29.12 to 160 mg/dL. Conclusion: Consequently, foot gymnastics can be integrated as an intervention for reducing blood sugar levels in diabetes mellitus patients. Keywords: Foot Gymnastic; Diabetes Mellitus